KNOWLEDGE MANAGEMENT IN ISLAMIC HIGHER EDUCATION (A Case Study on Implementation of Knowledge Management Tools in UIN SGD Bandung) - Lilis Sulastri; Hayder Al Hadey Ahmad Mohammed (Jurnal Pendidikan Islam, 2015)
The demand on the implementation of knowledge management is even greater at higher education institutions as an institution that intersect with many academic activities and the development of a scientific assessment as occurs in UIN Sunan Gunung Jati Bandung. This study tried to explore and analyze how UIN SGD Bandung run management practices and various activities in it, especially within the framework of the management of intellectual assets owned as an important step of applying the knowledge management. More specifically, this study used a qualitative approach with descriptive-holistic methods and case study analysis, have tried to analyze the use of knowledge management tools in UIN SGD Bandung. This study in its analysis found that there are many deficiencies essentially and conceptually in the implementation of knowledge management conducted by the management UIN SGD Bandung. Some knowledge management tools, such as technology infrastructure, collaboration tools, taxonomy, also has not been applied properly. However, the cycle of activities related to the conversion process of knowledge, such as socialization, externalization, combination, and internalization, has been done in UIN SGD Bandung.